Are all cafè-au-lait spots the brown skin macules? - Bonifazi, E. (European Journal of Pediatric Dermatology, 1997)
The report of Romiti et Al., in this issue of the Journal, should be discussed for two reasons as follows: 1- the definition of the hyperpigmented macules which are present from the first period of life and 2- the more general problem of the association between skin and other organs malformations (...).